บทบาทของคณะกรรมการตรวจสอบและติดตามการบริหารงานตำรวจ ระดับสถานีตำรวจ : ศึกษากรณีกองบัญชาการตำรวจนครบาล - ศุภชัย ประไพนพ (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The objectives of this research was to study the roles and supports of the Commission of Overseeing and Following-up Police Administration at practical level in Bangkok Metropolis. The samplings were composed of police officers belonging to the Metropolitan Police Bureau. Data obtained by interviewing 96 police officers and questionnaires were used to collect relevant information from 390 police officers. The analysis was done by SPSS program and statistics tools used to interpret the findings were in forms of percentage, means, standard deviation, chi-square test and anova test. The study found that the role of the Commission of Overseeing and Following-up Police Administration in Bangkok areas was in the medium level which the role of receiving the ways and policy from the commission inthe national level and Bangkok level was the highest role and the role of offering the suggestion, helping and supporting of police administration was the lowest role. In each Bangkok area, the mean level of the roles of the commission were different. The role of the Commission of Overseeing and Following-up Police Administration in the inner zone of Bangkok was the most outstanding followed by in the central zone and the outer zone respectively. The findigns was concordant with the concept of the ecology of crime system. The supports for police officers in different area were found indifferent in this study. In each Bangkok area, the activities related to prevention and suppression were mostly supported while the traffic police activity was least supported. It also found that the correlation of the roles and the supports of the Commission of Overseeing and Following-up Police Administration was in the same direction.